Conventional and field-assisted sintering of nanosized Gd-doped ceria synthesized by co-precipitation. Issue 10 (1st August 2016) - Biesuz, M.; Dell'Agli, G.; Spiridigliozzi, L.; Ferone, C.; Sglavo, V.M.
Abstract: Gadolinium-doped ceria is an attractive electrolyte for potential application in SOFCs operating at intermediate temperature; for such use, the fundamental compositions typically contain 10–20 mol% Gd2 O3 . In this work, we produced nanosized 10 mol% gadolinium-doped ceria powder by co-precipitation, starting from Ce and Gd nitrate solutions and using ammonia solution as precipitating agent. The co-precipitate was characterized by DTA-TG, TEM, XRD and nitrogen adsorption analyses. We studied the behavior of the nanopowder under both conventional and Flash sintering. Very different behavior was seen: the conventional sintering cycle produced a poorly densified material, while Flash sintering allowed production of a perfectly densified material, with uniform sub-micrometric grain size.